Pengembangan Platform Manajemen Proyek Kolaboratif Berbasis Web untuk Siswa Program Keahlian RPL di SMK - Naufal Albion; Isnandar; Syarif Suhartadi (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
This study aims to develop a web-based Collaborative Project Management Platform as a supporting learning media for the Basic Software Engineering subject in vocational high schools. This research used the Research and Development (R&D) method with the ADDIE development model, consisting of analyze, design, development, implementation, and evaluation stages. The research subjects consisted of one media expert, one material expert, and 34 tenth-grade students of the Software Engineering program at SMK Negeri 8 Malang. Data collection techniques used media expert validation questionnaires, material expert validation questionnaires, and user response questionnaires. The results showed that the media expert validation obtained a percentage of 98% with the “Very Valid” category, the material expert validation obtained 98.3% with the “Very Valid” category, and the user testing obtained 80.8% with the “Fairly Valid” category. These results indicate that the Collaborative Project Management Platform is feasible to be used as a collaborative project-based learning medium. The platform is able to support collaboration activities, task distribution, project progress monitoring, and assist teachers in monitoring students’ contributions during the learning process.